Designing a new clustering-based routing algorithm using a genetic algorithm to expand the lifetimeof the IoT network based on wireless sensors (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background: Energy is one of the main factors forcommunication in theInternet of Things based on sensors. Sensors are a low and non-rechargeableenergy source because sensors are commonly used in places and applicationswhere they cannot be recharged.Purpose: The most important goal of this study is to reduce the energyconsumption of sensors and increase the lifetime of the Internet of Thingsnetwork using genetic algorithm while selecting a clusterhead and routingbetween clusterheads.Methods: In this paper, after distributing nodes in the network, the geneticalgorithm is used to select the cluster heads and also to create a route betweenthe cluster heads to the base station. After selecting the cluster head by thegenetic algorithm, the normal nodes join thecluster head and send their data toit. After collecting the data and processing them, the data is transferred to thebase station from the route specified by the genetic algorithm.Results: The proposed algorithm is implemented with MATLAB simulator andcompared with LEACH, MB-CBCCP and DCABGA protocols. The simulationresults show that the proposed algorithm works better than the mentionedalgorithms in different environments.Conclusion: Due to energy constrained and the fact that in most applicationsthe batteries can not be recharged, the use of optimization algorithms indesigning and implementation of routing and clustering algorithms has asignificant impact on expanding the lifetime of these networks.